2005
DOI: 10.1182/blood-2004-06-2141
|View full text |Cite
|
Sign up to set email alerts
|

Heparanase promotes the spontaneous metastasis of myeloma cells to bone

Abstract: Although widespread skeletal dissemination is a critical step in the progression of myeloma, little is known regarding mechanisms that control metastasis of this cancer. Heparanase-1 (heparanase), an enzyme that cleaves heparan sulfate chains, is expressed at high levels in some patients with myeloma and promotes metastasis of some tumor types (eg, breast, lymphoma). Using a severe combined immunodeficient (SCID) mouse model, we demonstrate that enhanced expression of heparanase by myeloma cells dramatically u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 126 publications
(114 citation statements)
references
References 42 publications
3
107
1
2
Order By: Relevance
“…S1A), indicating that the increased level of acetylated histone in the HPSE-high cells is due to enhanced HAT enzyme activity, not to an increase in the amount of HAT present. Also, it is important to note that the level of heparanase expression and activity in the HPSE-high CAG cells is similar to that found in some myeloma patient tumors (23,24). Thus, the increase in HAT activity by these cells is not due to an enhancement of heparanase expression beyond levels that are likely to be found in the human cancer microenvironment.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…S1A), indicating that the increased level of acetylated histone in the HPSE-high cells is due to enhanced HAT enzyme activity, not to an increase in the amount of HAT present. Also, it is important to note that the level of heparanase expression and activity in the HPSE-high CAG cells is similar to that found in some myeloma patient tumors (23,24). Thus, the increase in HAT activity by these cells is not due to an enhancement of heparanase expression beyond levels that are likely to be found in the human cancer microenvironment.…”
Section: Resultsmentioning
confidence: 94%
“…Growing in Vivo-Because heparanase promotes tumor progression (24) and because regulation of histone modifications and HAT overexpression play a central role in cancer progression (14,29), we investigated whether the heparanase mediated up-regulation of HAT activity that we see in vitro is also present within tumors growing in vivo. Immunohistochemistry of tumor xenografts revealed that tumors formed by HPSE-high cells have high levels of acetylated histone H3 compared with cells within tumors formed by HPSE-low cells (Fig.…”
Section: Heparanase Enhances Acetylation Of Histone In Myeloma Tumorsmentioning
confidence: 99%
“…This cell line secretes human light chain, is Epstein-Barr virus negative, and will form tumors when injected subcutaneously in SCID mice (14). Cells were cultured in RPMI 1640 medium supplemented with 10% fetal bovine serum, 2 mM L-glutamine, 100 units/ml penicillin, and 100 g/ml streptomycin sulfate.…”
Section: Methodsmentioning
confidence: 99%
“…We applied our treatment subcutaneously, the likely site of application upon clinical translation. In addition to examining the injection site, we chose to analyze lung, liver and spleen based on previous studies determining the location of metastasis after subcutaneous tumor implantation [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Lungs and spleens weights were recorded, and livers were sectioned and examined for gross and microscopic lesions. Real-time PCR for ERV-3, a primate-specific 130 bp retrovirus present in known quantity in human cells, was utilized to detect and quantify persistent ASCs in select organs identified as primary sites of metastasis after subcutaneous tumorigenic application [13][14][15][16], as well as the injection site itself.…”
Section: Introductionmentioning
confidence: 99%